Korelasi Nilai Oktan dan Kandungan Oksigen Biofuel Mangrove dengan Brake Torque dan Emisi NOx Mesin Bensin 150cc - Syarifudin; Khumaidi Usman, Muhamad; Fatkhurrozak, Faqih; Lukman Sanjaya, Firman (Infotekmesin, 2025)
Alternative fuels are a priority to reduce the problem of fuel stock shortages. Bioethanol has potential because of its octane number specifications, oxygen content, and simple production techniques. Mangrove bioethanol is produced from mangrove fruit, which is non-edible and abundant. This study aims to observe the correlation of Mangrove Biofuel specifications (mixture of gasoline and 5% Mangrove Bioethanol) to Brake Torque and NOx Emissions produced by gasoline engines. Experimental methods are applied, from Mangrove Bioethanol production, octane value, oxygen content testing, and Mangrove Biofuel production to performance and emission testing. The results of the study showed that the correlation of the 101 octane number specifications and 30.31% oxygen content of Mangrove Biofuel increased the highest Brake Torque, reaching 5.45%, and increased the highest NOx emissions up to 6.54% at engine speeds of 5000 rpm.